Caracterização bioquímico-fisiológica de genótipos de batata (Solanum tuberosum) cultivados em solos com acúmulo de cobre - Farias, Júlia Gomes (2012)
Soils cultivated with grapevines and with a history of cupric fungicide application may accumulate copper, which may be toxic to plants. The ecotoxicological effects of copper (Cu) are a global concern; comparatively there is a lack of information relating phytotoxicity of heavy metals in plants with nutritional efficiency. This work aimed to study the process of stress induced by Cu excess, effect on the mineral nutrients distribution, and to define predictors of Cu toxicity in different tissues of potato genotypes, differing in the efficiency of use and response to phosphorus (P). Plants grown in vineyards soils with different levels of Cu (2.2, 5, 36.3, 67, 95.7, 270.5 and 320.70 mg kg-1) during periods of fall and spring growing season, in a greenhouse. Tissue Cu concentration was dependent on the external Cu level and the higher concentrations were observed in root and stolon tissues and most of absorbed Cu was accumulated in tubers. During the fall growing season, plants pre-classified as not efficient but responsible to P had the highest sensitivity to Cu excess in growth and nutritional terms. These responses included plants without expanded leaves and without tubers production, while genotypes pre-classified as efficient in the use of P were able to expand leaves and to produce tubers in all tested soils. During the fall growing season, there was an increase of malondialdehyde (MDA) concentration in leaves during the plant cycle in all tested soils. In addition, during the spring growing season, the concentrations of MDA and H2O2 were slightly different between the samples. The genotypes pre-classified as efficient and responsive to P showed a greater increase in H2O2 concentration in soils with high Cu, while genotype pre-classified as non-efficient and responsive to P showed a higher increase of H2O2 treatment with deficit P. In general, the enzymes tested, including ascorbate peroxidase, superoxide dismutase and catalase activities were increased with increasing external Cu. However, our results provide evidence that the antioxidant system was not sufficient to prevent biological damage by ROS in high concentrations of Cu, resulting in deleterious effects. Concentrations of P and Cu were highly correlated with Cu toxicity in Cambi soils, while Fe and K were more correlated in Ultisols. In addition, our data suggest the use of medians and apex leaves to investigate toxicity of Cu in potato plants. This study presents evidence of non-competitive uptake of Cu and Fe for the potato plants, and that the P efficiency of use confers greater tolerance to Cu excess.